Entrepreneurship in Higher Education : The effect of the entrepreneurial education agenda in entrepreneurial intention and the key role of self-efficacy - Ramalho, José Neves da Cruz Pereirinha (2020)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação